2020
DOI: 10.3390/sym12040586
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Dynamics of Viscoelastic Moving Rayleigh Beams with an Asymmetrical Distribution of Material Parameters

Abstract: In this article, vibration of viscoelastic axially functionally graded (AFG) moving Rayleigh and Euler-Bernoulli (EB) beams are investigated and compared, aiming at a performance improvement of translating systems. Additionally, a detailed study is performed to elucidate the influence of various factors, such as the rotary inertia factor and axial gradation of material on the stability borders of the system. The material properties of the beam are distributed linearly or exponentially in the longitudinal direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 47 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…In this paper, the Galerkin technique used to solve the vibration equations of a cracked graded Rayleigh beam. The general form of Galerkin technique is given as [31]:…”
Section: Solution Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, the Galerkin technique used to solve the vibration equations of a cracked graded Rayleigh beam. The general form of Galerkin technique is given as [31]:…”
Section: Solution Methodsmentioning
confidence: 99%
“…Raising the regression index of material property causes the drop in natural frequencies, while natural frequencies rise in the case of an increase in axial velocity as manifest in the results. A. Shariati et al [31], the vibration equation of the viscoelastic moving graded beam in which properties change axially based on exponential law distribution was derived according to Euler and Rayleigh models. The vibration equations were resolved by the Galerkin approach.…”
Section: H Ghayeshmentioning
confidence: 99%
See 1 more Smart Citation
“…This influence has direct effect on wing performances and therefore is considered as one of the challenging problems. The aeromechanical design instructions can be revealed from the study on positioning and instability of the ailerons [20] at the trailing edge of different wings which were conducted by researchers via the Finite volume method [21,22]. Dixon and Mei expanded the use of the applicable design methods for composite panels as they are considered common materials in aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported characteristic frequencies [1][2][3][4], modal localization and buckling [5][6][7][8][9][10][11][12][13][14], quasi-periodic distribution parameter effects [15][16][17][18] and application [19][20][21][22][23][24][25][26][27] based on transfer matrix method, spatial (Bloch) harmonic expansion method, (Floquet-Bloch and Galerkin) double expansion method and finite element method, etc. Waves and vibration in beams with non-uniform distribution parameters have also been pursued using a fundamental solution, semianalysis and finite element methods [28][29][30][31][32][33][34]. Perturbation and multiple scale methods were applied for weakly periodic parameter cases [35,36].…”
Section: Introductionmentioning
confidence: 99%